2015
DOI: 10.1021/acs.jafc.5b00377
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Inhibits the Isomerization of β-Carotene during Quenching of Singlet Oxygen and Free Radicals

Abstract: The present study aimed to investigate the influence of singlet oxygen and radical species on the isomerization of carotenoids. On the one hand, lycopene and β-carotene standards were incubated with 1,4-dimethylnaphthalene-1,4-endoperoxide that produced singlet oxygen in situ. (13Z)- and (15Z)-β-carotene were preferentially generated at low concentrations of singlet oxygen, while high concentrations resulted in formation of (9Z)-β-carotene. The addition of different concentrations of lycopene led to the same i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 54 publications
5
29
1
Order By: Relevance
“…PPIX has been detected in both the dermis and epidermis [106] and during both the quenching processes discussed here. All-trans β-carotene is converted to a cis-trans mixture, as has been observed previously and discussed above [87,88]. Since it is well established that cis isomers absorb light around 330 nm, some inner filter effects may arise from such cis isomers, which may somewhat increase the importance of this mechanism of protection and cis carotenoids quench 1 O 2 less efficiently than all-trans isomers [86], so the 1 O 2 quenching mechanism will be decreased.…”
Section: Singlet Oxygen-porphyriamentioning
confidence: 80%
See 1 more Smart Citation
“…PPIX has been detected in both the dermis and epidermis [106] and during both the quenching processes discussed here. All-trans β-carotene is converted to a cis-trans mixture, as has been observed previously and discussed above [87,88]. Since it is well established that cis isomers absorb light around 330 nm, some inner filter effects may arise from such cis isomers, which may somewhat increase the importance of this mechanism of protection and cis carotenoids quench 1 O 2 less efficiently than all-trans isomers [86], so the 1 O 2 quenching mechanism will be decreased.…”
Section: Singlet Oxygen-porphyriamentioning
confidence: 80%
“…It has also been established that all β-carotene isomers share a common triplet state, twisted about the middle carbon-carbon double bond, compared to the ground state [87]. Additionally, when using hexane as a solvent, it has been demonstrated that cis isomers are formed after the reaction of the all-trans isomers with 1 O 2 for both β-carotene and lycopene and, furthermore, that lycopene prevents β-carotene isomerization [88]. Since the absorption spectra of the cis isomers has an additional band-the so-called cis peak-this could affect the results from steady-state studies.…”
Section: Singlet Oxygen-simple Solvents Micelles and Liposomesmentioning
confidence: 99%
“…A time-resolved resonance Raman study has indicated that all β-carotene isomers share a common triplet state, twisted about the central carbon–carbon double bond compared with the ground state [ 43 ]. A recent study in hexane has shown that cis isomers are produced after reaction of the all- trans isomers with 1 O 2 for both lycopene and β-carotene and that lycopene can prevent β-carotene isomerization [ 44 ].…”
Section: Carotenoidsmentioning
confidence: 99%
“…Methoxylation of hydroxyl groups did not lead to any significant decrease of the 1 O 2 quenching activity, further proving that cycloaddition reaction of the carbon-carbon double bond plays an important role in quenching 1 O 2 , and it is more effective than the resorcinol ring. Several articles reported that the carotenoids have a strong activity of quenching 1 O 2 , closely related to the existence of conjugated double bonds [24,25]. Pallidol has the strong ability to quench 1 O 2 [15], but it does not contain any carbon-carbon double bond, only resorcinol rings.…”
Section: Resultsmentioning
confidence: 99%